Efektivitas Perangkat dan Alat Bantu Penglihatan Warna untuk Pasien Buta Warna: Analisis - Irfanya, Petra; Kartika, Antonia (PT Kalbe Farma Tbk., 2025)
Introduction: Color blindness, or color vision deficiency, is an eye condition that can reduce quality of life. Tinted contact lenses have been researched as a potential tool for correcting color blindness. Methods: This review aims to identify the effectiveness of color blindness aids and devices for patients with color vision deficiency as an alternative to enhance their quality of life. Article searches were conducted through electronic databases Google Scholar and PubMed using the keywords “color vision deficiency device,” “color blindness device,” and “color vision deficiency management.” Inclusion criteria included articles published between 2018-2023, full texts, writing in English, alignment of titles with abstracts, and validity of research methods. Results: The literature search yielded 98 articles; 8 articles met the inclusion criteria. Analysis of these 8 articles showed that color blindness devices and aids provide subjective new color perception and interpretation for color-blind individuals, but the objective effectiveness of these tools was not significant. Conclusion: The importance of public awareness of color blindness and the importance of developing more effective color-blind tools and devices. Further research is needed to develop color blindness devices and aids.